Peroxymonosulfate activation using CoFe2O4/Fe2O3 nanocomposite for Acid Orange removal - Mohamed Faisal Gasim; Qing-Sheng Gooi; Wen Da Oh (AMTS and Faculty of Engineering - Universitas Riau, 2022)
Herein, mixed–metal nanocomposite catalysts with various compositions (CoFe2O4/xFe2O3; x = 0, 0.25, 0.50, 0.75 and 1) were successfully fabricated by a co–precipitation method. The composition and morphology of the catalyst were systematically characterized. The catalyst with the highest Co content (CoFe2O4), exhibited the greatest efficiency for the acid orange 7 (AO7) degradation via peroxymonosulfate (PMS) activation. The effects of several experimental parameters including pH, CoFe2O4 loading, and PMS dosage on AO7 degradation were studied, and the catalytic activity was found to increase with the mentioned parameters. Moreover, CoFe2O4 displayed adequate reusability and was able to degrade AO7 for at least four consecutive cycles. In addition, the total organic carbon (TOC) removal of CoFe2O4 was determined while the catalyst stability was observed from the metal leaching in the treated solution. Furthermore, the magnetism of CoFe2O4 provides facile separation of the catalyst from the treated solution. Sulfate radicals (SO4•–) were identified as the main reactive species responsible for AO7 degradation.